PENGUATAN ORIENTASI KEWIRAUSAHAAN UMAT HINDU MELALUI KEUNGGULAN BERSAING BERBASIS LOCAL WISDOM PADA KELOMPOK TANI SARI KELA CEMPAKA DI DESA PEJENG KANGIN, TAMPAKSIRING, GIANYAR - Ni Luh Adisti Abiyoga Wulandari; Ni Komang Sumadi; I Gede Aryana Mahayasa; Cokorda Gde Bayu Putra; Ida Bagus Gede Parandita; Ni Kadek Sintha Rila Cahyani (UNHI Press, 2022)
The Sari Kela Cempaka farmer group was formed as an alternative activity due to the impact of the Covid-19 pandemic which destroyed the tourism industry in Tampaksiring District. This farmer group was formed as a forum for approximately 20 honey bee farmers. This farmer group has a problem with the lack of facilities and infrastructure in developing this farmer group so that it can become a good center for kele honey bee farmers in Pejeng Kangin village. Lack of sufficient knowledge about good honey bee cultivation, and the arrangement of cultivation sites, including harvesting bee honey products and marketing the products that have been produced. Currently, everything is still done conventionally and still on a very small scale. The farmers who are members of this farmer group have realized the potential of the products they produce and their marketing potential is very good. Based on the partners' problems, community service activities were carried out in the form of 1) procurement of kele honey bee colonies and a Honey Refractometer to increase the quantity and quality of production of kele honey produced, 2) assistance in modern honey bee cultivation, 3) counseling on the use of social media in activities product marketing, 4) training in the preparation of simple financial reports. This community service activity has positive implications for partners so that they can improve their current entrepreneurial orientation through competitive advantage based on local resources.